TORSION STRENGTH OF ROUND BAR A6061 FRICTION WELD JOINT INFLUENCED BY FRICTION TIME, UPSET FORCE AND ONE-SIDE CONE GEOMETRY - Yudy Surya Irawan; Wahyono Suprapto; Tjuk Oerbandono (Journal of Environmental Engineering and Sustainable Technology, 2017)
ABSTRACTEffect of friction time, upset force and one-side cone geometry on torsion strength of A6061 round bar friction weld joint was studied. Round bar commercial A6061 was friction welded with initial compression force of 2.5 kN on stationary part and the rotated part had revolution speed of 1600 rpm with variation of friction time of 45, 50 and 55 minutes. In the upset stage, the variation of upset force of 5 kN, 7.5 kN and 10 kN with the same upset holding time of 110 seconds. The stationary part of the specimen had friction area with variation of cone geometry that represented with ratio of upper diameter, D1 and lower diameter, D2, D1/D2. It was found friction time and the ratio of D1/D2 affected torsion strength in the upset force below 10 kN. In case of the higher upset force of 10 kN, the upset force more dominant to affect torsion strength of the continuous drive friction weld (CDFW) joint. The specimen with maximum torsion strength has more precipitates in grains of microstructures compared to that of specimen with lower torsion strength. Keywords: Continuous drive friction welding, aluminum, friction time, upset force, one-sdie cone geometry, torsion strength.